2022
DOI: 10.1080/00986445.2022.2026338
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sinusoidal fins’ amplitude on the thermo-hydraulic performance of a solar air heater

Zoheir Saboohi,
Fathollah Ommi,
Ebrahim Rahmani
et al.

Abstract: Solar energy exploitation is growing consistently, as it is the cheapest and most accessible amongst all forms of renewable energies. Increasing the performance of solar air heaters can aid in developing clean energy use and subsiding the greenhouse gas emissions from in the world. This study, therefore, seeks to improve the thermo-hydraulic performance of solar air heaters using sinusoidal extended surfaces. The results show that Reynolds number increment contributes to the enhancement of Nusselt number and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Rahmani et al [61] found an increase of 50% in the Nusselt number by increasing the sinusoidal fin height by 0.5 times the duct height. Similar results were found for wavy fins by Saboohi et al [62]. In the case of the relative height ratio (e/D), it was found that the Nu number and friction factor were raised by enhancing the relative rib height (e/D) for rectangular ribs, conical ribs, and equilateral triangular ribs, up to an optimum value of e/D [44][45][46].…”
Section: Absorber With Fins/ribssupporting
confidence: 82%
“…Rahmani et al [61] found an increase of 50% in the Nusselt number by increasing the sinusoidal fin height by 0.5 times the duct height. Similar results were found for wavy fins by Saboohi et al [62]. In the case of the relative height ratio (e/D), it was found that the Nu number and friction factor were raised by enhancing the relative rib height (e/D) for rectangular ribs, conical ribs, and equilateral triangular ribs, up to an optimum value of e/D [44][45][46].…”
Section: Absorber With Fins/ribssupporting
confidence: 82%